Tahlil Al-Akhta’ Al-Imlaiyyah Fii Ta’lim Al-Lughah Al-Arabiyah - Uliyanda, Dewi; Zulheddi, Zulheddi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
Writing correct dictation is one of the basic skills in learning Arabic. This study aims to analyze the forms of dictation errors of grade VIII students at the Al-Fauzi Fadillah Amal Galang Tahfidz Qur'an Islamic Boarding School, and to determine the factors causing dictation errors. This type of research is descriptive with a qualitative approach, by analyzing the documentation of students' dictation worksheets. Data were collected using documentation, observation and interview methods. The results of the study indicate that dictation errors still often occur, including: errors in writing hijaiyah letters because their sounds are almost the same, errors in the form of writing hijaiyah letters, errors in connecting and separating letters, and errors in writing tanwin. These errors are caused by linguistic factors; namely: There is new vocabulary that has never been heard and practiced in daily activities, lack of student ability regarding how to write correct Arabic, limited ability to distinguish the sounds of hijaiyah letters that are almost the same and lack of practice in writing hijaiyah letters. And non-linguistic factors; namely: Low interest or motivation in learning for students, non-conducive learning atmosphere, insufficient learning time, poor vision and hearing for students when teachers provide learning materials, and imla' learning which is still new to Arabic language learning.